Prognostic value of the H2FPEF score in patients undergoing transcatheter aortic valve implantation. (20th November 2020) - Ludwig, Sebastian; Pellegrini, Costanza; Gossling, Alina; Rheude, Tobias; Voigtländer, Lisa; Bhadra, Oliver D.; Linder, Matthias; Kalbacher, Daniel; Koell, Benedikt; Waldschmidt, Lara; Schirmer, Johannes; Seiffert, Moritz; et al.
Abstract: Aims: The aim of this study was to assess the prognostic value of the H2 FPEF score in patients undergoing transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS) and preserved left ventricular ejection fraction (EF). Methods and results: In this multicentre study, a total of 832 patients from two German high‐volume centres, who received TAVI for severe AS and preserved EF (≥50%), were identified for calculation of the H2 FPEF score. Patients were dichotomized according to low (0–5 points; n  = 570) and high (6–9 points; n  = 262) H2 FPEF scores. Kaplan–Meier and Cox regression analyses were applied to assess the prognostic impact of the H2 FPEF score. We observed a decrease in stroke volume index (−2.04 mL/m 2 /point) and mean transvalvular gradients (−1.14 mmHg/point) with increasing H2 FPEF score translating into a higher prevalence of paradoxical low‐flow, low‐gradient AS among patients with high H2 FPEF score. One year after TAVI, the rates of all‐cause (low vs. high H2 FPEF score: 8.0% vs. 19.4%, P  < 0.0001) and cardiovascular (CV) mortality (1.9% vs. 9.0%, P  < 0.0001) as well as the rate of CV mortality or rehospitalization for congestive heart failure (6.4% vs. 23.2%, P  < 0.0001) were higher in patients with high H2 FPEF score compared with those with low H2 FPEF score. After multivariable analysis, a high H2 FPEF score remained independently predictive of all‐cause mortality [hazard ratio 1.59 (1.28–2.35), P  = 0.018] and CV mortality or rehospitalization for congestive heart failure [hazard ratio 2.92 (1.65–5.15), P  < 0.001]. Among the H2 FPEF score variables, atrial fibrillation, pulmonary hypertension, and elevated left ventricular filling pressure were the strongest outcome predictors. Conclusions: The H2 FPEF score serves as an independent predictor of adverse CV and heart failure outcome among TAVI patients with preserved EF. A high H2 FPEF score is associated with the presence of paradoxical low‐flow, low‐gradient AS, the HFpEF in patients with AS. By identifying patients in advanced stages of HFpEF, the H2 FPEF score might be useful as a risk prediction tool in patients with preserved EF scheduled for TAVI.